Interface engineering towards low temperature in-situ densification of SOFC. (20th March 2020) - Wei, Lili; Dong, Wenjing; Yuan, Menghui; Xia, Chen; Xiao, Ziwei; Hu, Mengling; Wang, Baoyuan; Wang, Xunying; Zhu, Bin
Abstract: Electrolyte densification, which is often realized by high temperature sintering (i.e. >1000 °C), is an essential process for solid oxide fuel cell (SOFC). However, it is hard to achieve interfaces with high ionic conductivity because the interfaces between particles would be greatly eliminated during the sintering process. In this study, a novel interface engineering method is designed basing on capillary action to densify the electrolyte and at the meantime achieve ionic conductive interfaces at low temperature. A porous electrolyte layer is found to become dense during fuel cell operation when alkali metal hydroxide (AMH) is added to the NiO anode. The observation of improved open circuit voltage (OCV) indicates gas leakage has been eliminated after AMH modification. Raman images confirm that AMHs can be absorbed into the electrolyte layer when the operating temperature is higher than the melting point of AMH. In addition, using a lithiated metal oxide (i.e. LiNiO2 ) as the anode, cell performance is further improved. EIS proves that the existing of AMH in the cell may affect gas diffusion in the electrode, but it significantly reduces ohmic resistance due to better interfacial ionic conductivity of the electrolyte. This in-situ electrolyte densification method not only enables us to simplify fuel cell fabrication process and lower the fabrication temperature but also provides ways for maintaining interface conductivity. Graphical abstract: Image 1 Highlights: Capillary action is used for in-situ densification of electrolyte at low temperature. Adding alkali metal hydroxide in the anode enables electrolyte densification. High temperature sintering is eliminated from cell fabrication. Raman images help confirm the distribution of alkali metal compound. AMH in the cell reduces ohmic resistance.